Forming a Paradigm of Prophetic Law from the Perspective of Arkanul Bai’ah - Romi Saputra (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
The rational paradigm has long dominated the thinking of mankind in law, not to mention Indonesian legal experts and jurists. By basing a truth on the ratio, the rational paradigm assumes that reason is the only means to arrive at the goals and objectives in law. So it is not surprising that the rational paradigm brings out secularism, pluralism, liberalism, and even to atheism, because with the spirit of ratio it tries to penetrate the walls of sacredness (something that is fixed, holy, and permanent) in religion under the pretext of being critical. Therefore, a new paradigm is needed to balance this rational paradigm by developing a prophetic or transcendental paradigm. The prophetic/transcendental thought has also been developed by Kuntowijoyo, and his studies have been expanded by Indonesian scientists such as Prof. Abosori and Dr. Kelik Wardiono from Universitas Muhammadiyah Surakarta The prophetic paradigm as a new paradigm is still very possible to be studied and explored, so in this paper we will try to build a prophetic paradigm from the perspective of Arkanul Bai’ah which was initiated by Imam Hasan Al Bana as a charismatic ulema and recognized by the world for his knowledge. The problem in this paper is what is the form of the paradigm of prophetic law from the perspective of Arkanul Bai’ah? The research method used of research is descriptive analytical qualitative research, the approach used is a conceptual approach, while the data collection techniques come from the literature or this research is also called library research. The results of this study: ontology of prophetic law from the perspective of Arkanul Ba’iah is that the meaning of the law refers to the substance of Allah SWT (Allah Himself), so in understanding legal issues, it is obligatory to be guided by the Qur’an and Sunnah and use them as a benchmark in weighing the truth. Epistemologically, prophetic law views science and revelation as a unity that cannot be separated (integrated), when there is a conflict between revelation and reason, revelation must take precedence. Then in scientific development, it is necessary to pay attention to the framework that is tsawabit and mutaghayirat so that shari’ah and reason work according to the designation of their respective territories. And axiologically, prophetic law is useful in presenting benefit, justice, grace and wisdom.Keyword: Paradigm, Prophetic Law, arkanul bai’ah